Analisis Utang Pemerintah, PMA, Ekspor, Inflasi dan Pertumbuhan Ekonomi dengan Pendekatan Panel VAR - khubbi Abdillah (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2022)
This study aims to determine the causality relationship between variables, impulse response and variance decomposition of sources of development financing for a country in Asia from macroeconomic variables, namely government debt, foreign investment (FDI), exports, inflation and economic growth using the Panel VAR method and the operation of the STATA software. The impulse response results show that the shock of the government debt variable and inflation was responded positively by the economic growth variable. FDI and export variables responded negatively by the economic growth variable. The results of variance decomposition show that the export variable is a driving factor for economic growth in the Asian region.